Study of the Use of Probiotics in Provision of Nutrition of Kale Plant (Ipomonea aquatica) in Aquaponic Planting Systems - Setya Budi Santoso; Hadi Suhardjono Guniarti (Future Science)
Cultivation of urban vegetables using the aquaponic system can be taken into consideration in future agriculture because fish manure and fish food residues can become nutrients for plants after being modified by probiotics. The study aims to analyze the ability of various probiotics in decomposing fish droppings into nutrients available for growth of kale plants (Ipomoea aquatica) in aquaponic cultivation systems. The study was conducted at the Greenhouse UPN Veteran in East Java using a completely randomized design with four treatments: 1) without probiotics (A1), 2) A2, 3) A3, and 4) A4, and each treatment was repeated three times. Control is carried out by planting kale on soil media. The results showed 1). Kale plants planted with aquaponic systems have poor growth compared to those planted using soil media. 2). Probiotics used in the treatment for catfish farming do not affect kale plants. 3) The use of Probiotics (A2, A3, and A4) affects the growth of fish weight better than without the administration of probiotics (A1)